2019
DOI: 10.1055/s-0038-1677542
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications and Impact of Diabetes Mellitus Severity on Revision Total Knee Arthroplasty

Abstract: Total knee arthroplasty (TKA) is a common and effective treatment of knee osteoarthritis. As the amount of TKAs performed increases, so does the number of TKA failures and subsequent revisions. Diabetes mellitus (DM) has been shown to increase complications following orthopaedic procedures. For these reasons, it is important to understand the association between severity of DM and the risk of postoperative adverse events following revision TKA. A retrospective cohort study was conducted using the American Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
1
28
3
Order By: Relevance
“…The mean age of patients among the groups ranged from 63 to 70.1 years. In this meta‐analysis, 3 articles included participants undergoing total shoulder arthroplasty (TSA) 10, 13, 21 , 6 included total knee arthroplasty (TKA) 15, 20, 24, 27–29 , 2 included revision total knee arthroplasty (rTKA) 14, 15 , 1 included total hip arthroplasty (THA) 30 , and the rest of the studies included both TKA and THA 16, 18, 19, 22, 23, 25, 26 . The mean NOS score was 6.18 (maximum 9), suggesting that this meta‐analysis included high‐quality studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of patients among the groups ranged from 63 to 70.1 years. In this meta‐analysis, 3 articles included participants undergoing total shoulder arthroplasty (TSA) 10, 13, 21 , 6 included total knee arthroplasty (TKA) 15, 20, 24, 27–29 , 2 included revision total knee arthroplasty (rTKA) 14, 15 , 1 included total hip arthroplasty (THA) 30 , and the rest of the studies included both TKA and THA 16, 18, 19, 22, 23, 25, 26 . The mean NOS score was 6.18 (maximum 9), suggesting that this meta‐analysis included high‐quality studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles 27, 29 were excluded because there were too few participants and there was high heterogeneity in the sensitivity analysis. Two studies reported the proportion of IDDM patients in among TSA patients 10, 13, 21 , whereas 2 articles reported the proportion of IDDM patients among revision knee arthroplasty patients 14, 15 , 4 reported the proportion of IDDM patients among THA patients 16, 17, 26, 30 , 6 studies reported the proportion of IDDM patients among TKA patients 16, 18, 20, 24, 26, 28 and 1 study separately reported the proportion of IDDM patients among THA and TKA patients 16 . In addition, 4 studies separately reported the proportion of IDDM patients among THA and TKA patients 19, 22, 23, 25 .…”
Section: Resultsmentioning
confidence: 99%
“…32 Poor glycemic control in diabetic patients can contribute to adverse surgical outcomes, most notably with an increased risk for acute perioperative complications. 21,23,24 Lee et al reported increased medical complication rates, infection, and prolonged hospital length of stay in insulin-dependent diabetics. 23 While Maradit Kremers et al reported no difference in primary TKA failures among all diabetic patients, they noted an increased incidence of aseptic loosening among patients with elevated preadmis-sion blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…a Abbreviations: BMI, body mass index; CHF, congestive heart failure; DVT, deep vein thrombosis; PE, pulmonary embolism. a p < 0.01. b p < 0.05.these conditions exist individually 12,14,16,17,19,21,[23][24][25]30,31. In contrast to the study hypothesis, morbid obesity was not associated with an increased risk of reoperation or component revision.…”
mentioning
confidence: 97%
“…This is consistent with the findings of Gu et al, who reported that in revision TKA, IDDM was a risk factor for transfusion, while NIDDM was not found to have such an association. 56 The increased need for transfusions in diabetic patients may be explained by the fact that diabetes and metabolic syndrome have been reported to impair fibrinolysis and induce platelet dysfunction. 57 Further research is needed to elucidate the relationship between insulin dependence and transfusion requirements.…”
Section: Discussionmentioning
confidence: 99%